The emotional intelligence of the school principal and its relationship to the organizational climate from the teachers’ point of view (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to identify the degree of practicing emotional intelligence by public secondary school principals from the perspective of teachers in the North Taif Education Office and to identify the level of organizational climate in schools for public secondary school principals from the perspective of teachers in the North Taif Education Office. The study also aimed to reveal the statistically significant correlation between the average responses of sample members regarding the practice of emotional intelligence by school principals and the level of organizational climate in schools from the perspective of teachers, and to reveal the statistically significant differences between the average responses of sample members regarding the practices of public secondary school principals of emotional intelligence and the level of organizational climate from the perspective of teachers in the North Taif Education Office attributed to the difference in the variables (qualification and experience). The researcher used the quantitative approach in its two styles (survey and correlation), and the study community consisted of secondary school teachers in the North Taif Education Office in Taif Governorate, numbering (2296) teachers, and the study sample was chosen using the simple random sample method, which numbered (334) individuals, representing (14.55%) of the study community.The study concluded that the school principals' practice of emotional intelligence was (very high) from the teachers' point of view, and the dimension (social awareness) came in first place with a very high degree. The level of the organizational climate in schools for the principals of public secondary schools from the teachers' point of view in the North Taif Education Office came in (very high) and the dimension (communication style) came in first place with a very high degree. The results concluded that there is a high-value positive correlation between the degree of school principals' practice of emotional intelligence in the North Taif Education Office and the level of the organizational climate for teachers. In this study, the researcher recommends that program developers in the Ministry of Education design long-term programs to enhance and develop emotional intelligence practices, given the significant impact this approach has on creating a positive organizational climate within the school.
Keywords: Emotional Intelligence; Organizational Climate; Teachers